2021
DOI: 10.1126/science.abi9702
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic-like fabrication of metal ion–cured bioadhesives by mussels

Abstract: Mussel mooring made mighty by metals Mussels produce an exceptional proteinaceous adhesive so they can withstand waves and currents. Metal ions bound to modified tyrosine residues play an important role in reinforcing the adhesive. Priemel et al . brought together a variety of spectroscopy and microscopy techniques to study the cellular mechanisms involved in adhesive fabrication in mussels (see the Perspective by Wilker). They found that metal ion–rich vesicles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
134
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(147 citation statements)
references
References 42 publications
3
134
0
1
Order By: Relevance
“…3c ). Hence, our data suggest that the velvet worm slime may be added to the growing list of extracellular biological materials, including mussel fibers 41 , spider silk 42 , or squid beak 43 , whose biofabrication is mediated by intermediate phases formed by LLPS. Exploiting this mechanism, the velvet worm may be able to stockpile protein complexes in a concentrated state within the slime gland while at the same preventing their aggregation prior to fast ejection.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…3c ). Hence, our data suggest that the velvet worm slime may be added to the growing list of extracellular biological materials, including mussel fibers 41 , spider silk 42 , or squid beak 43 , whose biofabrication is mediated by intermediate phases formed by LLPS. Exploiting this mechanism, the velvet worm may be able to stockpile protein complexes in a concentrated state within the slime gland while at the same preventing their aggregation prior to fast ejection.…”
Section: Resultsmentioning
confidence: 87%
“…3c). Hence, our data suggest that the velvet worm slime may be added to the growing list of extracellular biological materials, including mussel fibers 41 , spider silk 42 , or squid beak 43 , whose biofabrication is mediated by intermediate phases formed by LLPS.…”
Section: Updated Fiber Formation Modelmentioning
confidence: 87%
“…The specific localization of the different protein building blocks within the complex plaque structure has been an area of intense experimental effort with more details emerging over the last decade or so. Biochemical and spectroscopic investigations revealed that D r a f t the bulk trabecular scaffold is comprised primarily of mfp-2, which consists of 11 tandem repeats of a ~45-residue long epidermal growth factor (EGF) motif, and that these DOPA-rich proteins (~5 mol%) are cross-linked via DOPA-metal interactions (likely Fe/V and Ca) [103][104][105] . Conversely, MALDI analysis of plaque footprints remaining after plaque removal showed that mfp-3, mfp-5 and mfp-6 were localized nearest the plaque-substrate interface 35 .…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Tamarin showed in 1976 that there are cilia-lined channels running through the phenol gland termed the longitudinal ducts (LDs), and that during induced thread formation, the contents of the vesicles are secreted through the LDs into the distal depression 97 . For nearly 50 years, there was not much further analysis of the LDs until very recent work by Harrington's group which combined histology, confocal Raman imaging, TEM and FIB-SEM to follow the plaque formation 105 . Most interesting was the discovery of the metal storage particles (MSPs) which contain concentrated Fe and V stabilized by catechol coordination.…”
Section: Phenol Gland (Plaque)mentioning
confidence: 99%
See 1 more Smart Citation